Writing (new) worlds: poetry and place in a time of emergency. Issue 4 (2nd October 2022) - Cresswell, Tim
ABSTRACT: It may appear that the act of writing is fruitless in the face of the size and open-ended complexity of gathering environmental calamities including global heating, species extinction, and the appearance of plastic in everything. And yet – and yet – poets and others continue to write in ways that allow us to think about the earth's futures and, more specifically, the future of place in catastrophic times. Geo, Eco and Topo – poetics are acts of making – making earth, home, and place. Making earth as homeplace. This paper considers Juliana Spahr's book Well Then There Now as an entry point into thinking and writing about place in a relational way appropriate for a time of emergency. It focuses on the ways writing-as-making (poiesis) can help us to diagnose troubled worlds and prefigure new ones. The paper surveys the connections between geography and poetry, outlines the contributions of eco, geo and topo poetics and explores the hybrid poetics of Well Then There Now before advocating for the affordances of creative writerly approaches for geography more broadly.